Doing multicultural education for achievement and equity - Grant, Carl A.; Sleeter, Christine E., 1948- (New York : Routledge, 2011)
'Doing Multicultural Education for Achievement and Equity a hands-on, reader-friendly multicultural education textbook, actively engages education students in critical reflection and self-examination as they prepare to teach in increasingly diverse classrooms. In this engaging text, Carl A. Grant and Christine E. Sleeter, two of the most eminent scholars of multicultural teacher education, help pre-service teachers develop the tools they will need to learn about their students and their students communities and contexts, about themselves, and about the social relations in which schools are embedded. Doing Multicultural Education for Achievement and Equity challenges readers to take a truly active and ongoing role in promoting equity within education and helps to guide them in becoming highly qualified and fantastic teachers. Features and updates to this much-anticipated second edition include: Reflection boxes that encourage students to actively engage with the text and concepts, along with downloadable templates available on Routledge.com 'Putting It into Practice' activities that offer concrete suggestions for really'doing' multicultural work in the classroom Fictional vignettes that illustrate the real issues teacher education students face and the ways their own cultural attitudes can impact their response New coverage of issues pertaining to student achievement, federal and state policy, and socioeconomic connections between the current economy and educational funding A more comprehensive discussion about the different social movements that have affected education in the past and present '--
'Doing Multicultural Education for Achievement and Equity, a hands-on, reader-friendly multicultural education textbook, actively engages education students in critical reflection and self-examination as they prepare to teach in increasingly diverse classrooms. In this engaging text, Carl Grant and Christine Sleeter, two of the most eminent scholars of multicultural teacher education, help pre-service teachers develop the tools they will need to learn about their students and their students' communities and contexts, about themselves, and about the social relations in which schools are embedded. Doing Multicultural Education for Achievement and Equity challenges readers to take a truly active and ongoing role in promoting equity within education and helps to guide them in becoming highly qualified and fantastic teachers. Features and updates to the much-anticipated second edition include: - Reflection boxes that encourage students to actively engage with the text and concepts, along with downloadable templates available on Routledge.com. -'Putting It into Practice' activities that offer concrete suggestions for really'doing' multicultural work in the classroom - Fictional vignettes that illustrate the real issues teacher education students face and the ways their own cultural attitudes can impact their response - New coverage of issues pertaining to student achievement, federal and state policy, and socioeconomic connections between the current economy and educational funding - A more comprehensive discussion about the different social movements that have affected education in the past and present'--
Includes bibliographical references (p. 253-265) and index.
Keywords: Multicultural education -- United States; Educational equalization -- United States; Student teachers -- Training of -- United States